English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-07 21:06:37 · 4 answers · asked by Thomas and M 1 in Science & Mathematics Mathematics

4 answers

(3/3)x - 9 + x - 2/3 - x
= 1x - 9 + x - 2/3 - x
= x + x - x - 9 - 2/3
= x - 29/3

2006-12-07 21:16:19 · answer #1 · answered by horensen 4 · 0 0

x=9 2/3

2006-12-08 05:12:28 · answer #2 · answered by efm 3 · 0 1

1/x -9 2/3

2006-12-08 05:12:01 · answer #3 · answered by Anonymous · 0 0

3/3x-9+x-2/3-x
=3/3x-9-2/3
=1/x-9 2/3

2006-12-08 05:16:49 · answer #4 · answered by pigley 4 · 0 0

fedest.com, questions and answers